BUILDING RELIGIOUS CHARACTERS OF THE 21ST CENTURY MUSLIM GENERATION - Maryatin, Teni; Syihabuddin, Syihabuddin; Sauri, Sofyan; Somad, Momod Abdul (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2020)
This research is motivated by the students’ low thinking ability shown by the results of the aqeedah understanding test with an average value of 57.1. The test was conducted on 212 randomly selected Muslim students of UNIKOM. The purpose of this research is to strengthen the way of thinking in improving faith (aqeedah) to build the religious characters of the 21st century Muslim students. Building the characters was done by developing aqeedah learning model aqeedah in PAI course using Talaqqiyan Fikriyyan Method based on rational thinking. This Research and Development (R&D) research used the ADDIE model. The stages were preliminary studies, model development, and model testing. Data were collected using observation, interview, literature study, questionnaire, and test. The results showed that students’ level of thinking ability increased. The average value of the posttests of the experimental class was 73.75 and the control class was 60.18. These results indicated that the use of the model made significant difference.